Copper-catalyzed cascade reactions of α,β-unsaturated esters with keto esters - Li, Zhengning; Wang, Chongnian; Li, Zengchang (Beilstein Journal of Organic Chemistry, 2015)
A copper-catalyzed cascade reaction of α,β-unsaturated esters with keto esters is reported. It features a copper-catalyzed reductive aldolization followed by a lactonization. This method provides a facile approach to prepare γ-carboxymethyl-γ-lactones and δ-carboxymethyl-δ-lactones under mild reaction conditions.
Keywords: aldol addition; cascade reaction; catalysis; conjugate reduction; copper; lactonization

(untitled) - Le Floch, C.; Le Gall, E.; Léonel, E.; Martens, T.; Cresteil, T. (Bioorg. Med. Chem. Lett., 2011)

(untitled) - Blanc, D.; Madec, J.; Popowyck, F.; Ayad, T.; Phansavath, P.; Ratovelomanana-Vidal, V.; Genet, J.-P. (Adv. Synth. Catal., 2007)

(untitled) - Pohmakotr, M.; Issaree, A.; Sampaongoen, L.; Tuchinda, P.; Reutrakul, V. (Tetrahedron Lett., 2003)

(untitled) - Barros, M. T.; Maycock, C. D.; Ventura, M. R. (Org. Lett., 2003)

(untitled) - Pohmakotr, M.; Sampaongoen, L.; Issaree, A.; Tuchinda, P.; Reutrakul, V. (Tetrahedron Lett., 2003)

(untitled) - Pohmakotr, M.; Soorukram, D.; Tuchinda, P.; Prabpai, S.; Kongsaeree, P.; Reutrakul, V. (Tetrahedron Lett., 2004)

(untitled) - Manoni, F.; Cornaggia, C.; Murray, J.; Tallon, S.; Connon, S. J. (Chem. Commun., 2012)

(untitled) - Drioli, S.; Felluga, F.; Forzato, C.; Nitti, P.; Pitacco, G. (Chem. Commun., 1996)

(untitled) - Lumby, R. J. R.; Joensuu, P. M.; Lam, H. W. (Org. Lett., 2007)

(untitled) - Le Floch, C.; Bughin, C.; Le Gall, E.; Léonel, E.; Martens, T. (Tetrahedron Lett., 2009)

(untitled) - Le Floch, C.; Le Gall, E.; Léonel, E.; Koubaa, J.; Martens, T.; Retailleau, P. (Eur. J. Org. Chem., 2010)

(untitled) - Le Floch, C.; Laymand, K.; Le Gall, E.; Léonel, E. (Adv. Synth. Catal., 2012)

(untitled) - Bazin, S.; Feray, L.; Vanthuyne, N.; Siri, D.; Bertrand, M. P. (Tetrahedron, 2007)

(untitled) - Li, Z.; Zhang, Z.; Yuan, L.; Jiang, L.; Li, Z.; Li, Z. (Synlett, 2014)

(untitled) - Li, Z.; Feng, Y.; Li, Z.; Jiang, L. (Synlett, 2014)

(untitled) - Boldrini, G. P.; Savoia, D.; Tagliavini, E.; Trombini, C.; Umani-Ronchi, A. (J. Org. Chem., 1983)

(untitled) - Zhao, D.; Oisaki, K.; Kanai, M.; Shibasaki, M. (Tetrahedron Lett., 2006)

(untitled) - Deschamp, J.; Chuzel, O.; Hannedouche, J.; Riant, O. (Angew. Chem., Int. Ed., 2006)

(untitled) - Li, Z.; Jiang, L.; Li, Z.; Chen, H. (Chin. J. Chem., 2013)

(untitled) - Sass, D. C.; de Lucca, E. C., Jr; da Silva Barbosa, J.; de Oliveira, K. T.; Constantino, M. G. (Tetrahedron Lett., 2011)